Patient personality and psychotherapist reactions in individual psychotherapy setting: a systematic review. (17th April 2020) - Stefana, Alberto; Bulgari, Viola; Youngstrom, Eric A.; Dakanalis, Antonios; Bordin, Chiara; Hopwood, Christopher J.
Abstract: Despite the importance of psychotherapists' subjective experiencse working with patients with mental issues, little is known about the relationship between therapists' emotional reactions and patients' personality problems. The present study is a systematic review of quantitative research on the association between patients' personality pathology and psychotherapists' emotional, cognitive and behavioural reactions in individual psychotherapy setting. A systematic database search (from January 1980 to August 2019) supplemented by manual searches of references and citations identified seven relevant studies. Significant and consistent relationships were found between therapist reactions and specific personality traits or disorders. In general, odd and eccentric patients tend to evoke feelings of distance and disconnection; emotionally dysregulated patients tend to evoke anxiety and incompetence, and anxious and withdrawn patients tend to evoke sympathy and concern. However, the relatively small sample of studies and methodological inconsistencies across studies limit firm conclusions and suggest the need for more systematic research. Findings from this review indicate that patients who share the same personality disorder or symptoms tend to evoke specific and similar cognitive, emotional and behavioural reactions in their therapists. This suggests that therapists overall reactions toward patients may be source of valuable diagnostic information.